'ReConnect': a model for working with persistent pain patients on improving sexual relationships. Issue 2 (May 2020) - Edwards, Sarah; Mandeville, Anna; Petersen, Katrine; Cambitzi, Julia; Williams, Amanda C de C; Herron, Katherine
Introduction: Many individuals with persistent pain experience difficulties with sexual function which are exacerbated by avoidance and anxiety. Due to embarrassment or shame, sexual activity may not be identified as a goal for pain management programmes (PMPs). In addition, clinicians can feel that they lack skills and confidence in addressing these issues. Methods: We sought to develop a biopsychosocial model for helping patients return to sexual activity and manage relationships in the context of pain management, known as 'ReConnect'. The model amalgamates well-established methods from pain management and sex therapy to guide multidisciplinary team members. ReConnect comprises three components: (1) 'cognitive and myth-busting', (2) 'sensations and feelings' and (3) 'action-experimentation'. We collected self-report data from 281 women and 92 men from our specialist PMP for chronic abdomino-pelvic. pain, including questions measuring interference with and avoidance of sex due to pain, and the Multi-dimensional Sexuality Questionnaire (MSQ) to measure anxiety about sexual activity. Results: The results show statistically significant improvements for anxiety, avoidance of sex and sexual interference. Using the ReConnect model to structure clinical work, pain management clinicians reported increased confidence in addressing sexual activity goals. Conclusion: By using the ReConnect model is a framework for clinicians to use to support sexual activity goals. It has demonstrated improvements in clinical outcomes such as anxiety around sex and interference of pain in sexual activity. We encourage its application in pain management services in both one-to-one and group sessions, as a method for encouraging pain patients to address this important area of life which can be adversely affected by pain.